Public Service Responsiveness: Handling Homeless People with Psychotics in the UPTD Liponsos Keputih Surabaya - Reviandani, Oktarizka; Djurubassa, Gloria Miagina Palako; Bataha, Katerina (Publik : (Jurnal Ilmu Administrasi), 2023)
Surabaya City is the largest population center of people with severe mental disorders (ODGJ) in East Java Province where the number of ODGJ Surabaya City increased in 2019 from 5503 people to 5519 people in 2020. The increasing number of ODGJ or psychotic vagrants affects the development and growth of the country both in terms of health, social, economic, human rights (HAM) and so on. This research was conducted using qualitative methods with a case study approach. This study aims to explain the responsiveness of the Surabaya City government, especially the Social Office in maximizing the UPTD Liponso Keputih Surabaya by looking at the elements of speed, accuracy, and clarity of public services in dealing with the problem of homeless people with psychotic people in the city of Surabaya. The results of this study show that Liponsos' ability to respond to the community is good, as seen from its commitment to deal with the problems of people with social welfare problems, especially homeless people with psychotics by compiling operational service standards that are measurable and strengthened by Mayor Regulation Number 36 of 2016 starting from the speed and accuracy of service, as well as clarity of service in accordance with standard operating procedures.